Community Participation Model in Household-Based Waste Management Synergy in Singojuruh Village Banyuwangi Regency - Jauhariyah, Nur Anim; Syafa’at, Ahmad Munib; Aziziy, Muhammad Riza (Proceedings of Annual Conference on Community Engagement, 2022)
Household waste is a complex problem because based on the results of a study that 76% of waste in the village comes from the kitchen in the form of organic waste and 24% in the form of inorganic. The purpose of this service is to build synergy between the community and the government to manage household-based waste as a source of additional income. This service approach uses Participatory Action Research (PAR). The results of the service show that every household that plays a role in disposing of waste is a housewife. So far, housewives still mix kitchen waste with plastic waste and then throw the garbage in the river or burn it. Household synergy with the government is very meaningful in answering the waste problem in Singojuruh Village, Banyuwangi District, with education on sorting waste from households, utilizing waste that has economic value, and disposing of residual waste through waste collection services.